Associations among health literacy, anxiety symptoms, and health-related quality of life in Korean adults: A cross-sectional study with age-stratified analyses - Gyuri Seol; Young Hwangbo; Yongbae Kim; Youngs Chang; Mee-Ri Lee (PLoS ONE, 2026)
Background Health literacy (HL) is a key determinant of physical and mental health outcomes; however, the relationships among HL, anxiety symptoms, and health-related quality of life (HRQoL) remain unclear, and whether the effects of HL vary by age is unknown. We aimed to examine the associations among HL, anxiety symptoms, and HRQoL in Korean adults and assessed age-related differences in these associations. Methods In this cross-sectional study, we analyzed data from the 2023 Korea National Health and Nutrition Examination Survey, including 5,017 adults aged ≥ 19 years. HL was assessed using a validated 10-item instrument (score range: 10–40) and categorized as low, middle, or high. Anxiety symptoms and HRQoL were measured using the 7-item Generalized Anxiety Disorder Scale and the 8-item Health-related Quality of Life Instrument, respectively. Multivariable logistic regression models adjusted for potential confounders were used to estimate associations between HL and anxiety symptoms and between HL and good HRQoL. Age-stratified analyses were conducted for participants aged 19–39, 40–64, and ≥ 65 years. Results The low (odds ratio [OR]: 1.93; 95% confidence interval [CI]: 1.52–2.46; p < 0.001) and middle HL (OR: 1.30; 95% CI: 1.04–1.62; p = 0.024) groups had higher odds of anxiety symptoms than the high HL group. Lower HL was associated with a reduced likelihood of good HRQoL (OR: 0.49; 95% CI: 0.36–0.66; p < 0.001), whereas the middle HL group showed a non-significant trend toward poorer HRQoL (OR: 0.77; 95% CI: 0.56–1.06). HL was associated with anxiety symptoms in young and middle-aged adults, and with HRQoL in young and older adults. Conclusion Low HL was significantly associated with increased anxiety symptoms and poor HRQoL, with a significant impact among young adults. These findings highlight the need for age-specific public health strategies to improve HL.